DEDIKASI GURU HONORER TK DAN DUKUNGAN MASYARAKAT DI ACEH BARAT: MENGATASI RENDAHNYA GAJI DEMI PENDIDIKAN ANAK USIA DINI - Karuni Humairah Arta; Arfriani Maifizar; Said Nazaruddin; Arizul Suwar (LPPM Universitas Cipta Mandiri, 2026)
Honorary Kindergarten teachers in remote areas of West Aceh face the challenge of low salaries ranging from IDR 50,000–250,000 per month, which depend on tuition fees of IDR 10,000–20,000 collected from 18–25 students per kindergarten, as well as limited opportunities to become civil servants (PNS) or government employees under work agreements (PPPK). This study aims to identify the motivations of honorary teachers, the role of community support, and its impact on the learning of Islamic values, as well as to provide policy recommendations based on Islamic values. Using a qualitative approach with a mini-ethnographic design, data were collected through interviews with 6 honorary teachers and 4 parents from four kindergartens in Arongan Lambalek and Woyla Barat Districts, observations in two kindergartens, and documentation. The results show that honorary teachers are dedicated to early childhood education during the golden age period, reflecting the value of sincerity (ikhlas) (Qur'an, Al-Bayyinah: 5), despite being constrained by low salaries and having side jobs such as selling fried snacks, farming, or sewing. Farming and fishing communities provide assistance in the form of food, agricultural products, or fish, reflecting ta’awun (mutual assistance) (Qur'an, Al-Maidah: 2), but this does not address the systemic problems. Low welfare conditions contradict the principle of justice (Qur'an, An-Nisa: 58). Recommendations include increasing regional budget (APBD) allocations for salaries, expanding PPPK quotas, providing entrepreneurship training, strengthening ta’awun, and improving PIAUD facilities. This study emphasizes the importance of teacher welfare for the quality of Islamic early childhood education in remote areas.